ISLAMIC COMMUNITY IN SICILY HISTORICAL HERITAGE AND THE MAJOR CHALLENGES OF THE PRESENT TIMES (Религиски дијалог и соработка, 2022)
: Islamic communities play a pivotal role in today’s Sicily. Islamis relevantnow,as it was in the Middle Ages. During Arabic occupation (827- 1060), this Islandwas partofIslamic world as en emirate. Muslims continued to be influential even in subsequent timesunder Norman (1060- 1094) and Hohenstaufen rulers (1194-1266). After this multiculturalperiod of toleration, Aragonese and Spanish occupation lead to oblivion of theIslamicpast. The repressed memory of Muslim Sicily dissimulated the absence of otherness since14th and 15th century. In the second half of the 20th century, Islamic presenceinSicilynoticeably increased. Apart from individual conversions, we must consider migrationfrom North Africa and Middle East. Subsequently, well-established communities arenowespecially active in many Sicilian towns. They play an important part in cooperationwithRoman Catholic Church and other religious groups. It is noteworthy to valueinitiativesaimed at promoting interreligious dialogue. At this respect, there are remarkableactivities under the patronage of the Islamic Centre in Messina with the support ofthelocal Archbishopric. I focus on a conference held in the city mosque in October 2019inthe presence of the President of Islamic Community and local Catholic Archbishop. Atthe occasion, the presenters discussed the encounter between Saint Francis of Assisi andSultan Malik al-Kāmil height hundred years before. This historical example is seentodayas an antecedent of interreligious meetings that equally applies for the present times. Thistopic offered the way of better considering religious dialogue in Mediterraneanspaceaccording to transcultural perspectives which emerge in a globalized world.